2016
DOI: 10.1007/s00726-016-2180-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory studies of the potential anti-cancer effects of creatine

Abstract: Two experiments were performed, in which male Wistar Walker 256 tumor-bearing rats were inoculated with 4 × 10(7) tumor cells subcutaneously and received either creatine (300 mg/kg body weight/day; CR) or placebo (water; PL) supplementation via intragastric gavage. In experiment 1, 50 rats were given PL (n = 22) or CR (n = 22) and a non-supplemented, non-inoculated group served as control CT (n = 6), for 40 days, and the survival rate and tumor mass were assessed. In experiment 2, 25 rats were given CR or PL f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 41 publications
3
26
0
Order By: Relevance
“…Suppressed expression of GATM in RCC tumors [4] is in line with recent findings of decreased excretion of guanidinoacetate (GAA) in RCC patients [21]. Interestingly, several studies have demonstrated that creatine inhibits growth of tumor cells both in vitro and in vivo [22][23][24]. The exact mechanism by which creatine attenuates cancer growth is unknown; however, possible mechanisms include inhibition of glycolysis or generation of acidosis [25].…”
Section: Discussionsupporting
confidence: 63%
“…Suppressed expression of GATM in RCC tumors [4] is in line with recent findings of decreased excretion of guanidinoacetate (GAA) in RCC patients [21]. Interestingly, several studies have demonstrated that creatine inhibits growth of tumor cells both in vitro and in vivo [22][23][24]. The exact mechanism by which creatine attenuates cancer growth is unknown; however, possible mechanisms include inhibition of glycolysis or generation of acidosis [25].…”
Section: Discussionsupporting
confidence: 63%
“…ATP and PCr can then diffuse back into the cytosol and help buffer energy needs. This coupling also reduces the formation of reactive oxygen species (ROS) and can therefore act as a direct and/or indirect antioxidant [3235]. The CK/PCr energy shuttle thereby connects sites of ATP production (glycolysis and mitochondrial oxidative phosphorylation) with subcellular sites of ATP utilization (ATPases) in order to fuel energy metabolism [24, 25, 27].…”
Section: Metabolic Rolementioning
confidence: 99%
“…In this regard, creatine supplementation has been reported to help lower cholesterol and triglyceride levels [67, 196]; reduce fat accumulation in the liver [197]; reduce homocysteine levels [198]; serve as an antioxidant [199–202]; enhance glycemic control [132, 203205]; slow tumor growth in some types of cancers [32, 198, 206, 207]; increase strength and/or muscle mass [37, 41, 44, 45, 82, 208212]; minimize bone loss [211, 212]; improve functional capacity in patients with knee osteoarthritis [213] and fibromyalgia [214]; positively influence cognitive function [43, 83, 195]; and in some instances, serve as an anti-depressant [215–217]. …”
Section: Potential Medical Uses Of Creatinementioning
confidence: 99%
“…The mechanisms underlying spontaneous regression are not entirely clear but may involve development of an adaptive immune response (Pardoll and Topalian, 1998; Rees and Mian, 1999), differential propagation of tumor sub clones in their microenvironment (Khong and Restifo, 2002) and consequent elimination by immune cells, antibodies, cytokines, and chemokines (Dunn et al, 2002, 2006; Bui and Schreiber, 2007; Jaganjac et al, 2008). Physical activity of the animals, exercise (Hoffman et al, 1962; Deminice et al, 2016b), dietary factors (Bekesi and Winzler, 1970; Kwong et al, 1984; Luty et al, 2016), or hormonal levels (Khegai, 2013; Khegay and Ivanova, 2015) may influence the regression of these cells or inhibit the activities driven by these cells (Campos-Ferraz et al, 2016; Cruz et al, 2016; Deminice et al, 2016a; Fracaro et al, 2016; Toneto et al, 2016). In most studies, tumor regression is generally overlooked as the tumor-bearing rats are sacrificed before regression is evident (Guimarães et al, 2010).…”
Section: Regression Of Tumor and Resolution Of Painmentioning
confidence: 99%